Efficiency of Life Insurance Companies: An Empirical Study in Nepal - Tandukar, Bikesh (Journal of Insurance Studies in South Asia, 2024)
The efficiency of life insurance companies is a critical aspect of their performance, influencing their ability to meet the needs of policyholders and shareholders alike. This empirical study examines the efficiency of life insurance companies in Nepal, focusing on key performance indicators such as the number of employees, paid-in capital and surplus, insurance contract liabilities, net premium written, and total invested assets. Using data from eight life insurance companies operating in Nepal from 2018 to 2022, we employ frontier efficiency analysis to evaluate firm performance against the 'best-practice' frontier determined by the top-performing firms in the industry. The results indicate that the efficiency scores of the companies range from 0.05 to 0.99, with some companies consistently demonstrating higher efficiency over the years. Correlation analysis reveals a positive relationship between the variables measuring efficiency, with premiums showing a particularly strong correlation with other variables. Regression analysis further confirms the significance of these relationships, with the model explaining 90.69% of the variation in total investments in assets by life insurance companies. The findings suggest that factors such as the number of employees, paid-in capital, insurance contract liabilities, and net premiums play a significant role in determining the efficiency of life insurance companies in Nepal. Companies with larger numbers of contracts and longer operating periods tend to be more efficient, highlighting the importance of scale and experience in the industry. Overall, this study provides valuable insights into the efficiency of life insurance companies in Nepal, contributing to the ongoing discourse on the development and sustainability of the sector. The findings can inform policymakers, industry stakeholders, and researchers in their efforts to enhance the effectiveness of the life insurance sector, ultimately benefiting policyholders and the broader economy.